2008
DOI: 10.1021/cg070635a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Gold Cuboid and Decahedral Nanoparticles Regulated and Controlled by Cu2+ Ions

Abstract: It is found that Cu 2+ is an effective agent for the controlled preparation of shaped gold nanoparticles. As the concentration of Cu 2+ increases from 0 mM to 0.2 mM to 1.6 mM, the shape of the gold nanoparticles changes from rod to cuboid to decahedron. A possible mechanism based on selectively retarding the growth rate of the {111} plane is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 35 publications
3
62
0
5
Order By: Relevance
“…The measured interplanar spaces for all lattice fringes from high-resolution transmission electron microscopy images correspond to the values obtained from electron diffraction and XRD data [18,19]. As an example, the measured interplanar space of 2.35 Å is in good agreement with the (1 1 1) lattice plane of face-centered-cubic (fcc) of gold [18,19]. The surface energy (γ) associated with different crystallographic facets of fcc metal types is described as follows: γ(1 1 1) < γ(1 0 0) < γ(1 1 0) [20].…”
Section: • Spherical Gold Nanoparticlessupporting
confidence: 76%
See 1 more Smart Citation
“…The measured interplanar spaces for all lattice fringes from high-resolution transmission electron microscopy images correspond to the values obtained from electron diffraction and XRD data [18,19]. As an example, the measured interplanar space of 2.35 Å is in good agreement with the (1 1 1) lattice plane of face-centered-cubic (fcc) of gold [18,19]. The surface energy (γ) associated with different crystallographic facets of fcc metal types is described as follows: γ(1 1 1) < γ(1 0 0) < γ(1 1 0) [20].…”
Section: • Spherical Gold Nanoparticlessupporting
confidence: 76%
“…The kinetic growth in the {100} direction seems to be superior to that in the {1 1 1} direction, which promotes the development of (1 1 1) facets. The measured interplanar spaces for all lattice fringes from high-resolution transmission electron microscopy images correspond to the values obtained from electron diffraction and XRD data [18,19]. As an example, the measured interplanar space of 2.35 Å is in good agreement with the (1 1 1) lattice plane of face-centered-cubic (fcc) of gold [18,19].…”
Section: • Spherical Gold Nanoparticlessupporting
confidence: 74%
“…It could therefore allow electrocatalytic reactions with great selectivity. The details of the synthesis process were reported elsewhere [5,14,16,28]. .…”
Section: Nanoparticles Preparationmentioning
confidence: 99%
“…The preferential adsorption of CTAB on the gold surface allows the preparation of nanoparticles with specific shape and surface crystallographic orientation. It is found that some metallic cations added to the growth solution, such as Cu 2+ or Ag + , are effective agents that favor the control of the NPs' shape [14,16]. In fact, Cu 2+ ions are adsorbed on (111) facets, selectively retarding their growth rate and preferentially leading to a particle growth along (100) facets [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation